Association between kinesiophobia and bone mineral density in hospitalized older adults with osteoporosis: a cross-sectional study - Tian, MengPing; Lv, WanQiu; Miao, XinLing; Chen, Cheng; Xiong, Jian; Zhang, Jiali (Frontiers in Endocrinology, 2026)
ObjectiveTo examine the association between kinesiophobia (fear of movement) and lumbar spine Bone mineral density (BMD) among hospitalized older adults with osteoporosis.MethodsThis cross-sectional study included 246 hospitalized adults aged 60 years or older with osteoporosis who were admitted to orthopedic wards at the Affiliated Hospital of Chengdu University between August and October 2025. Kinesiophobia was assessed using the 17-item Tampa Scale for Kinesiophobia (TSK-17), with scores ≥37 indicating the presence of kinesiophobia. The primary outcome, volumetric trabecular bone mineral density (BMD), was measured at the lumbar spine (L1–L4) using quantitative computed tomography (QCT). Spearman correlation and multivariable linear regression analyses were performed to evaluate factors associated with BMD.ResultsAmong 246 participants (53 men,193 women),186 (75.6%) exhibited kinesiophobia. CT-measured BMD was significantly lower in participants with kinesiophobia (p < 0.001). Kinesiophobia showed a moderate negative correlation with BMD (ρ = –0.286, p < 0.001), while age demonstrated a strong negative correlation (ρ = –0.443, p < 0.001), and BMI a weak positive correlation (ρ = 0.148, p = 0.02). In multivariable analyses, kinesiophobia was independently associated with lower BMD (β, −8.897 mg/cm³; 95% CI, −13.715 to −4.079; P <.001). Older age was also associated with lower BMD (per 1-year increase: β, −0.516 mg/cm³; 95% CI, −0.694 to −0.338; P <.001). The overall model explained 20.1% of the variance in BMD.ConclusionAmong hospitalized older adults with osteoporosis, kinesiophobia was independently associated with lower bone mineral density. These findings underscore the clinical relevance of assessing and addressing fear of movement as part of comprehensive osteoporosis care in hospitalized older adults.